Cymbochasma borysthenica (Pall. ex Schlecht.) Klokov et Zoz in the Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The resultes of the species investigations and its preading in Ukraine – all the locations known from the literature and herbarium material and the new location are given. The ecologycal and coenotyc peculiarities and desciption history of the Cymbochasma borysthenica are given. In all the coenoses it has low level association with turf grass. For protection of this rare species it was proposed to create nature reserves in its all known location in Kherson and Mykolajiv region.
Keywords: Cymbochasma borysthenica, rare species.